Revolutionizing ghee production through Moringa Oleifera SP. flavor infusion (ID110) - Asogan, Arjun; Norazlianie, Sazali (Penerbit UTHM, 2024)
This study presents an innovative approach to ghee production, integrating Moringa oleifera sp. leaves to enhance storage, flavor, and fragrance, with added medicinal benefits. The process, involving boiling, fermenting, churning, and simmering, is complemented by a Lactobacillus plantarum culture and a unique Moringa infusion. The study explores ultrasonic cream separation, an eco-friendly technology inducing specific frequencies for instantaneous separation of fat particles. Despite its efficiency, the study addresses cream skimming inefficiencies, proposing optimal solutions. The resulting product not only showcases improved aroma and texture but also addresses health concerns such as mobility issues, gastrointestinal disorders, and excessive weight. With 75 kg already sold directly, this fusion of gastronomy and wellness resonates with a discerning market. This research contributes significantly to advancing both ghee production and dairy technology, aligning seamlessly with the evolving preferences of health-conscious consumers.